Myeloid-derived suppressor cells: The green light for myeloma immune escape. Issue 5 (September 2016) - Malek, Ehsan; de Lima, Marcos; Letterio, John J.; Kim, Byung-Gyu; Finke, James H.; Driscoll, James J.; Giralt, Sergio A.
Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous, immature myeloid cell population with the ability to suppress innate and adaptive immune responses that promote tumor growth. MDSCs are increased in patients with multiple myeloma (MM) and have bidirectional interaction with tumors within the MM microenvironment. MM-MDSCs promote MM tumor growth and induce immune suppression; conversely, MM cells induce MDSC development and survival. Although the role of MDSCs in infections, inflammatory diseases and solid tumors has been extensively characterized, their tumor-promoting and immune-suppressive role in MM and the MM microenvironment is only beginning to emerge. The presence and activation of MDSCs in MM patients has been well documented; however, the direct actions and functional consequences of MDSCs on cancer cells is poorly defined. Immunosuppressive MDSCs play an important role in tumor progression primarily because of their capability to promote immune-escape, angiogenesis, drug resistance and metastasis. However, their role in the bone marrow (BM), the primary MM site, is poorly understood. MM remains an incurable malignancy, and it is likely that the BM microenvironment protects MM against chemotherapy agents and the host immune system. A growing body of evidence suggests that host immune cells with a suppressive phenotype contribute to a myeloma immunosuppressive network. Among the known suppressor cells, MDSCs and T regulatory cells (Tregs) have been found to be significantly increased in myeloma patients and their levels correlate with disease stage and clinical outcome. Furthermore, it has been shown that MDSC can mediate suppression of myeloma-specific T-cell responses through the induction of T-cell anergy and Treg development in the MM microenvironment. Here, we review clinical correlations and the preclinical proof-of-principle data on the role of MDSCs in myeloma immunotolerance and highlight the mechanistically relevant MDSC-targeted compounds and their potential utility in a new approach for anti-myeloma therapy.